Cross-cultural Comparison on Customers Preference for Configurators in China and Germany - Wang, Ning; Wang, Kanliang (International Journal of Industrial Engineering and Management, 2016)
The promising configurator development in collectivist country like China calls for more focus on how to design good featured configurators according to different cultural background. This paper examines four characteristics the design of configurators in China should differ from their German counterparts.This paper has combined two research methods. First, an online survey is implemented with 72 respondents in each country. Afterwards, 2 Chinese focus groups (16 participants in total) and 2 German focus groups (16 participants in total) are implemented to validate the result from online survey. Results show that Chinese tend to have positive attitude on social features embedded in configurators such as “asking professional designers or friends for feedback” and “sharing final design via social media”, while Germans tend to have negative attitude towards these social features. Moreover, Chinese customers have significant preference difference on valuing the feature of “the most popular option”. However, on the feature of “starting from most popular designs created by other customers or from professional designers”, there is no significant cultural different reflected, while customers in both countries tend to have positive attitude towards starting from professional’s designs. Article history: Received (07.11.2016); Revised (28.11.2016); Accepted (23.12.2016)